The Reservation Debate in India: Balancing Constitutional Mandates and Socio-Economic Realities (Samsad Journal संसद जर्नल, 2025)
Indian society has a complex social structure and is primarily separated into different castes, religious & linguistic communities, and tribes. The exclusion of the untouchables marks the beginning of India's reservation policy history. Due to their uneven and hierarchical disadvantages, which are marked by institutional discrimination and inequality, the untouchable castes have been and/or continue to be the most oppressed. India’s reservation system was constituted conferring to the Constitutional Provisions to elevate the deprived and marginalized sections and give them their rights. It is explicitly stated in the Articles- 15(4), 15(5), and 15(6) of the Indian Constitution. Many studies point out that reservation has been instrumental in endorsing upward mobility and social equity. However, the underprivileged segments of society still face barriers to social mobility. The current paper covers the detail exploration of the reservation scheme as enshrined in the Indian Constitution. Analysis of the past literature in the pertinent areas and facts collected from secondary sources, it has been emphasized that the reservations should be sustained but modified to meet needs of diverse communities, and granted to those who genuinely require them till they achieve equality in socio-cultural, educational, economic, and political spheres. Although there remains a door for discussion and amendment, it is determined that India's reservation system has been influential in improving the lot of underprivileged groups. While it provides necessary affirmative action, there is a growing call for policy modifications to ensure fair and effective distribution of benefits.